Community Empowerment through Financial Literacy and Management to Build Sustainable MSMEs in Solok Regency, West Sumatra - Wahyu Indah Mursalini; Afni Yeni; Esi Sriyanti; Arfimasri Arfimasri; Mohamed Ayyub Hassan (LPPM Universitas PGRI Sumatera Barat, 2026)
Understanding the basic concepts of financial literacy and management of MSMEs in Solok Regency is still low, resulting in slow economic growth. The purpose of this study to analyze how community empowerment through financial literacy and management can build sustainable MSMEs in Solok Regency. The research method used is a quantitative approach, with MSMEs in the food and beverage sector as the unit of analysis. The data used are primary data, collected using purposive sampling through surveys and questionnaires from 90 respondents using a Likert scale. Data analysis uses statistical analysis with the Multiple Linear Regression method using the SPSS program, whose stages include: validity, reliability, t, f, and determination tests. The results show that the interaction of financial literacy and management complement and strengthen each other in influencing to performance MSMEs the food and beverage sector in Solok Regency. Between the two variables, financial literacy has a significant influence on MSME performance. Financial management practices demonstrate the need for awareness of the importance of good financial management. However, there is still room for improvement, particularly in financial education, the use of technology, and the development of a more formal management system. Theoretically, the concept of innovation and sustainable knowledge in financial management will enable MSMEs to make wise decisions for the sustainability of their businesses. Practically, these findings imply the importance of training and support from the government or relevant institutions. Therefore, this study makes a significant contribution to community empowerment in MSME development, economic growth, and national development. With an increasingly complex economy and the needs of individuals, groups, and governments, it is crucial for MSME performance to be managed and adapted to developments in science and technology.